Biosynthesis of gold nanoparticles using plant extracts and their application in photothermal therapy of cancer - Ilona Szymańska; Monika Richert (Polish Pharmaceutical Society, 2024)
Gold nanoparticles (AuNPs) have tremendous therapeutic potential in various biomedical fields, such as targeted therapy, radiotherapy, phototherapy and cancer diagnostics. The unique physicochemical properties of AuNPs depend on the size, shape, aggregation, surface charge and functionalization of their surface. The type and conditions of synthesis here have a significant impact on these parameters. Biosynthesis using plant extracts makes it possible to obtain environmentally friendly gold nanoparticles with greater stability and better biocompatibility than those obtained by a chemical process. Bioactive components of plant extracts, in addition to reducing properties, also play a stabilizing role for nanoparticles. Moreover, their specific biological activity may act synergistically with the anticancer properties of AuNPs. Photothermal therapy (PTT) is a promising method for treating cancer due to its low-invasive nature, high selectivity and precision. Nanoparticles are usually used as photothermal agents due to their properties. The use of gold nanoparticles, obtained and modified by biosynthesis from plant extracts, in photothermal cancer therapy (PTT) can reduce the toxicity of nanoparticles and increase the therapeutic efficacy of this method. The combination of biosynthesized gold nanoparticles, which can act as non-toxic carriers of drugs and biomarkers, with photothermal therapy and imaging techniques (e.g.: computed tomography, X-ray) represent potentially effective theranostic agents for cancer treatment. The purpose of this study is to analyze the literature data and to introduce the novel and current issue of the application of biogenic AuNPs in photothermal cancer therapy.Based on the current research, the biosynthesis of AuNPs using plant extracts was described and the parameters that had a significant impact on their physicochemical properties, which determine the toxicity, biocompatibility, biodistribution and stability of nanoparticles, were characterized. Furthermore, the cytotoxic activity of biogenic AuNPs on exemplary cancer cell lines was demonstrated, and the advantages and disadvantages of biosynthesis and promising results of clinical studies on the use of gold nanoparticle products in cancer therapies were presented.